2008
DOI: 10.1002/ptr.2392
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and antimicrobial activity of medicinal plants from Ghana: Cassia sieberiana, Haematostaphis barteri, Mitragyna inermis and Pseudocedrela kotschyi

Abstract: The antimicrobial activity of the sequential n-hexane, acetone and 50% aqueous methanol extracts of leaves, stem bark and roots of four species of medicinal plants, Cassia sieberiana DC. (Leguminosae), Haematostaphis barteri Hook. f. (Anacardiaceae), Mitragyna inermis (Willd.) O. Kuntze (Rubiaceae) and Pseudocedrela kotschyi (Schweinf.) Harms (Meliaceae), from Ghana were tested against Bacillus subtilis, Pseudomonas syringae and Cladosporium herbarum using TLC direct-autobiographic methods. Extracts from leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 16 publications
4
40
0
1
Order By: Relevance
“…In many African communities, the knowledge on medicinal plant usage is often transmitted from the older generation to the younger via word-of-mouth (orally) and most of this knowledge has not been documented (Sofowora, 1993;Asase et al, 2008Asase et al, , 2010. This situation is worsened by the general tendency of deforestation in some of these communities which would irremediably lead to the disappearance of valuable and rare medicinal plants.…”
Section: Introductionmentioning
confidence: 95%
“…In many African communities, the knowledge on medicinal plant usage is often transmitted from the older generation to the younger via word-of-mouth (orally) and most of this knowledge has not been documented (Sofowora, 1993;Asase et al, 2008Asase et al, , 2010. This situation is worsened by the general tendency of deforestation in some of these communities which would irremediably lead to the disappearance of valuable and rare medicinal plants.…”
Section: Introductionmentioning
confidence: 95%
“…This knowledge is often transmitted from one generation to another usually via word-of-mouth, and as such the traditional uses of many species of plants have not been documented (Asase et al, 2008). There is danger of losing this precious knowledge due to the rapid degradation of natural habitats and ecosystems leading to loss of plant and cultural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have shown that various extracts have antimicrobial and antifungal activities (Asase et al, 2008); analgesic, anti-inflammatory, antiparasitic, antimalarial, myorelaxant, antispasmodic, and antisickling activities (Duwiejua et al, 2008;Sy et al, 2009;Fatokun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%